Evaluasi Perilaku Tanah Dasar Embung Rano Tadulako terhadap Pengaruh Gempa - Rodiah , Fiisyatin; Sarika , Hardiyanti; Amaliah , Rizki; Warliawati , Sri; Andjani, Ni Made Ayu Juli (Universitas Kristen Indonesia Paulus, 2025)
Palu City is an earthquake-prone area, notably marked by the September 28, 2018 earthquake (Mw 7.4) which caused significant damage. Rano Tadulako Reservoir serves as a crucial raw water supply for Tadulako University, necessitating evaluation of its subgrade stability against seismic effects. This study evaluates subgrade stability through dynamic bearing capacity analysis using the pseudostatic method. Primary data includes Cone Penetration Tests at 4 points across 20 cross-sections, while secondary data comprises seismic parameters showing PGA = 0.919 g. Analysis involved calculating horizontal seismic coefficient (kh = 0.46), ultimate bearing capacity using Terzaghi's method, and seismic capacity reduction. Results show 84% of the reservoir (16 of 19 segments) meets safety criteria with SF ≥ 1.5, ranging from 0.150 to 7.402. Critical points were identified at segments 9-10 with SF = 0.150. Overall, the subgrade is relatively safe, though local reinforcement and continuous monitoring are essential for long-term stability.